2014
DOI: 10.1080/14634988.2014.942590
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and intraseasonal variability of surface chlorophyll a concentration in the South China Sea

Abstract: Seasonal and intraseasonal variability of surface chlorophyll a concentration in the South China Sea is explored using the NASA standard Sea-Viewing Wide Field-of-View Sensor (SeaWiFS) monthly and 8-day level-3 products from 1997 to 2007. The link between the seasonal and intraseasonal variability of the chlorophyll and physical forcing is revealed. Continuous wavelet transform indicates that chlorophyll in the South China Sea presents pronounced seasonal, as well as intraseasonal, variability. Chlorophyll a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…With the advent of abundant satellite remote sensing ocean color data, seasonally high chlorophyll a concentration (Chl a) has been found in the wind-driven upwelling or jet areas northeast of Luzon Island and southeast of Vietnam [Tang et al, 1999;. Although Chl a is not equivalent or linearly proportional to phytoplankton concentration [Cullen, 2015], it has been taken as one proxy or indicator of phytoplankton biomass because of its indispensable role in the photosynthesis of phytoplankton [e.g., Tang et al, 2004Tang et al, , 2014. Some synoptic scale phytoplankton blooms caused by typhoons were also observed via surface Chl a variation in the open SCS [Lin et al, 2003;Shang et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…With the advent of abundant satellite remote sensing ocean color data, seasonally high chlorophyll a concentration (Chl a) has been found in the wind-driven upwelling or jet areas northeast of Luzon Island and southeast of Vietnam [Tang et al, 1999;. Although Chl a is not equivalent or linearly proportional to phytoplankton concentration [Cullen, 2015], it has been taken as one proxy or indicator of phytoplankton biomass because of its indispensable role in the photosynthesis of phytoplankton [e.g., Tang et al, 2004Tang et al, , 2014. Some synoptic scale phytoplankton blooms caused by typhoons were also observed via surface Chl a variation in the open SCS [Lin et al, 2003;Shang et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Satellite remote sensing data show that surface Chl a in the SCS exhibits a pronounced seasonal variation [Shen et al, 2008;Palacz et al, 2011;Tang et al, 2014]. Based on monthly mean SeaWiFS data during the period of September 1997 to December 2006, Shen et al [2008] demonstrated that in the northern SCS Chl a reached its maximum (larger than 0.3 mg m 23 ) in winter and minimum (0.1-0.15 mg m 23 ) in summer.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations